Favipiravir in Patients With Early Mild-to-moderate Coronavirus Disease 2019 (COVID-19): A Randomized Controlled Trial. (6th September 2022) - Golan, Yoav; Campos, Jesus Abraham Simon; Woolson, Rob; Cilla, Donald; Hanabergh, Rodolfo; Gonzales-Rojas, Yaneicy; Lopez, Reynaldo; Finberg, Robert; Balboni, Armand
Abstract: Background: Despite vaccination, many remain vulnerable to coronavirus disease 2019 (COVID-19) and its complications. Oral antivirals to prevent COVID-19 progression are vital. Based on perceived potency and clinical efficacy, favipiravir is widely used to treat COVID-19. Evidence from large randomized controlled trials (RCT) is lacking. Methods: In this multicenter double-blinded placebo-controlled RCT, adults with early mild-to-moderate COVID-19 were 1:1 randomized to favipiravir or placebo. The study evaluated time to sustained clinical recovery (TT-SCR), COVID-19 progression, and cessation of viral shedding. Results: Of 1187 analyzed patients across 40 centers, 83.3% were Hispanic, 89.0% unvaccinated, 70.3% severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) seronegative, and 77.8% had risk factors for COVID-19 progression. The median time from symptom presentation and from positive test to randomization was 3 and 2 days, respectively. There was no difference in TT-SCR (median of 7 days for both groups; P = .80), COVID-19 progression [11 patients each (1.9% vs 1.8%); P = .96], time to undetectable virus (median = 6 days, 95% confidence interval [CI] [6–8] vs 7 days, 95% CI [6-9]), or in undetectable virus by end of therapy (73.4% vs 72.3%; P = .94). Outcomes were consistent across the analyzed sub-groups. Adverse events were observed in 13.8% and 14.8% of favipiravir-treated and placebo-treated subjects, respectively. Uric acid elevation was more frequent among favipiravir-treated subjects (19.9% vs 2.8%). Conclusions: Favipiravir was well tolerated but lacked efficacy in TT-SCR, progression to severe COVID-19, or cessation of viral shedding and should not be used to treat patients with COVID-19. (Supported by Appili Therapeutics) Clinical Trials Registration: NCT04600895 Abstract : Favipiravir has been endorsed and widely used for coronavirus disease 2019 (COVID-19) around the world. Data from adequately powered randomized controlled trials (RCTs) is lacking. Our double-blind RCT demonstrates a lack of efficacy of favipiravir in mitigating COVID-19 symptoms, preventing progression, and shutting viral shedding.